Trends, perspectives, opportunities and challenges with sensor technology in wintersports - Stöggl, T.; Snyder, C.; Buchecker, M.; Thorwartl, C. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
Recent developments in sensor technology have made sensing units cheaper and easier to implement. These developments have made the application of "wearable technology", or smart sporting equipment appealing to a broad audience allowing measuring metrics of motion quantity (e.g. distance, time, number of cycles) and motion quality, or how well a sport technique is performed. In the current presentation the concept of an instrumented ski boot, an instrumented alpine ski using the PyzoFlex® sensor foil technology and the determination of force components and measures of effectiveness within various cross-country skiing (XCS) techniques applying a push-off model is presented.